Pemikiran Politik Benazir Bhutto Tentang Negara Dan Perempuan - Intan Khalizah Sirait (Dinamika Politik, 2013)
This study is about the concept of consideration of Benazir Bhutto about State and woman. Focus to background the emergence of consideration of state and woman by Benazir Bhutto. There are two important things as result of this study: First, there are paradigm Islam consider that Islam is one of ideology or basic of existence a State. Second, woman reputed has great participation on sproduction and implementation politic decision. Method of this study use descriptive-qualitative method purpose to describe a incident with more detail. Kata Kunci: Political Thought, state, woman.